The correlation of whole blood viscosity and outcome in mechanical thrombectomy for acute ischemic stroke - Thapa, Monika; Courville, Jordyn; Leonhard, Reese; Buchhanolla, Prabandh; Sheikh, Mohammad Abdurrehman; Shah, Rahul; Rai, Prashant; Chokhawala, Himanshu; Hossain, Md Ismail; Bhuiyan, Mohammad Alfrad Nobel; Jordan, J. Dedrick; Kelley, Roger E. (Frontiers in Stroke, 2025)
IntroductionWhole blood viscosity (WBV), reflecting the intrinsic resistance of blood flow, is an established predictor of stroke events in individuals. This study aims to correlate the WBV at different shear rates with the outcome of mechanical thrombectomy, known to be an effective treatment for large vessel occlusion (LVO) stroke.MethodThis is a single-center retrospective study conducted at our comprehensive stroke center. The charts of 317 patients who underwent mechanical thrombectomy within 6 h of LVO stroke presentation were reviewed. The modified Rankin score (mRS) at discharge was used as the outcome measure, with individuals categorized as low (0–2) or high (3–6). WBV at different shear rates was calculated using De Simone's Formula. The T-test and Chi-square test were used to compare baseline continuous and categorical data, respectively, amongst the mRS study groups. We utilized multivariable logistic regression analyses to identify the independent risk factors associated with the outcome of interest following mechanical thrombectomy. In addition, Spearman rank order correlation was used to assess for r value between mRS and WBV at different shear rates.ResultsBaseline group characteristics, including demographics and medical history, were similar among the two study groups. Of note, our study found no significant differences in clinical outcomes between the two groups with WBV at high shear rate (OR 0.969, 95% CI 0.77–1.204, p = 0.780) and low shear rate (OR 0.998, 95% CI 0.988–1.008, p = 0.779) following mechanical thrombectomy. Spearman rank order correlation between mRS at discharge with WBV at high shear rate (r = 0.058, p = 0.123) and low shear rate (r = 0.048, p = 0.128) was non-significant.DiscussionThere is limited information of the effect of WBV at high and low shear rates on the clinical outcome following mechanical thrombectomy in patients with LVO. Our results revealed that WBV at high and low shear rates did not impact the functional outcome of mechanical thrombectomy. This result might be affected by the potential limitation of the formula used to derive the given shear rates. Despite this lack of association observed in our study, other contributors of viscosity may still potentially play a significant role in outcome following mechanical thrombectomy.